The Role of Children's Literature in the Training of Competitive Personnel - Ashurova Zulkhumor Shodiyevna (Research Parks Publishing LLC, 2021)
This article examines the role and place of children's literature in the years of independence in the training of qualified personnel. The analysis of the poem